Type II-Metacaspases are involved in cell stress but not in cell death in the unicellular green alga Dunaliella tertiolecta - M. Teresa Mata; Armando Palma; Candela García-Gómez; María López-Parages; Víctor Vázquez; Iván Cheng-Sánchez; Francisco Sarabia; Félix López-Figueroa; Carlos Jiménez; María Segovia (Microbial Cell, 2019)
Ultraviolet radiation (UVR; 280–400 nm) has a great impact on aquatic ecosystems by affecting ecophysiological and biogeochemical processes as a consequence of the global change scenario generated by anthropogenic activities. We studied the effect of PAR (P)+UVA (A)+UVB (B) i.e. PAB, on the molecular physiology of the unicellular green alga Dunaliella tertiolecta for six days. We assessed the relationship between the triggered UVR stress response and metacaspases and caspase-like (CL)activities, which are proteases denoted to participate in cell death (CD) in phytoplankton. UVR inhibited cell growth and in vivo chlorophyll a fluorescence but did not cause cell death. Western blot analyses reflected that Type-II metacaspases (MCs) are present and appear to be involved in UVR induced-cell stress but not in dark-induced CD in D. tertiolecta. Enzyme kinetics revealed that cleavage of the MCs-reporter substrates RVRR, QRR, GRR, LKR, HEK, and VLK was 10-fold higher than WEHD, DEVD, IETD, and LETD CLs-substrates. The lowest apparent Michaelis-Menten constants (KMap) corresponded to RVRRase (37.5 µM) indicating a high affinity by the RVRR substrate. The inhibition of enzymatic activities by using inhibitors with different target sites for hydrolyses demonstrated that from all of the R/ Kase activities only RVRRase was a potential candidate for being a metacaspase. In parallel, zymograms and peptide-mass fingerprinting analyses revealed the identities of such Rase activities suggesting an indirect evidence of possible natural physiological substrates of MCs. We present evidence of type II-MCs not being involved in CD in D. tertiolecta, but rather in survival strategies under the stressful irradiance conditions applied in this study.